Evaluation of the antigenotoxic and antioxidant activity induced by croton antisyphiliticus - da Silva, Regildo Márcio Gonçalves [UNESP]; Figueiredo, Célia C.M. [UNESP]; Gomes, Amanda C. [UNESP]; Ferreira, Paulo C. [UNESP]; Granero, Filipe O. [UNESP]; Santiago, Patrícia S. [UNESP]; Silva, Luciana P. (FapUNIFESP (SciELO), 2020)
This study aimed to investigate antigenotoxicity and antioxidant potential of extract, fractions and vitexin from C. antisyphiliticus. Methanolic extract was fractionated through solvents of increasing polarity. The composition of extracts and fractions were evaluated through phytochemical screening. Micronucleus test was performed in mice to evaluate the antigenotoxicity. Antioxidant activity was measured using the assay 1,1-diphenyl-2-picrylhydrazyl (DPPH), iron ion chelating, thiobarbituric acid assay and nitric oxide scavenging. Treatment with extract, fractions and vitexin did not produce an increase in Micronucleus mean values. However, Micronucleus (MN) mean values decreased in relation to control. methanolic extract presented antioxidant potential for DPPH (81%), iron ion chelating (77.8%), Thiobarbituric Acid (TBARS) (32.49%) and Nitric Oxide (NO) (80.97%). Ethyl acetate fraction showed the highest antioxidant activity (65.46%). The vitexin showed a Inhibitory Concentration (IC50) of DPPH value smaller in relation to control. Vitexin flavonoid was detected by High Performance Liquid Chromatography (HPLC), infrared spectrometry and nuclear magnetic resonance. It can be inferred that methanolic extract, fraction ethyl acetate and vitexin isolated from C. antisyphiliticus is endowed with antigenotoxic and antioxidant potential.
Keywords: Cytotoxicity; DPPH; Flavonoids; Mice; Micronucleus; Phenolic content